A post-season short duration mesocycle for tapering in water-polo - Botonis, P.; Toubekis, A.; Platanou, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: In water-polo, although elite coaches` experience has been reported (Mujika, 2009), no scientific evidence exist regarding methods of effective tapering prior to a series of critical matches usually playing post-season. The aim of the present study was to examine the effectiveness of a fourweek mesocycle, including an overloaded (week 1 and 2) and a reduced training load periods (week 3 and 4), on wellness, swimming performance and perceived internal training load (ITL) in water-polo players preparing for play-offs. Methods: Eight national-level waterpolo players (age: 25±7 years, body height: 181±5 cm, body mass: 84±7 kg) participated in the study. ITL was estimated using the session-RPE method and perceived ratings of wellness (e.g. fatigue, muscle soreness, sleep quality, stress level and mood) (Hooper & Mackinon, 1995) were assessed daily. Sport-specific performance was evaluated through 400-m and 20-m tests performed before (baseline) and after overloading training as well as at the end of reduced training load phases. Analysis of variance for repeated measurements on dependent samples was employed to detect differences between training phases. A Tukey post-hoc test was used for multiple comparisons. Correlation coefficient (r) was used to test the associations between changes ( ) in performance variables and the respective changes in ITL, wellness, sleep quality, fatigue perception muscle soreness, stress level and mood state across the training weeks. Statistical significance was set at p<0.05. Results: In week 3 and 4, ITL was reduced compared to week 1 by 19.0±3.8% and 36.0±4.7%, respectively (p=0.00 and p=0.00). Wellness was significantly improved in week 4 compared to weeks 1 and 2 (p=0.00). At the end of the mesocycle, swimming performance at 400-m and 20-m tests was improved compared to baseline (0.8±0.6% and 2.1±2.2%, respectively, p<0.05) and overloading training period (1.3±0.8% and 2.5±2.8%, respectively, p<0.05). High correlations were observed between the percentage reduction of ITL (week 4-1) and the respective changes in 20 m swim time (r=0.88, p<0.01), in fatigue perception, muscle soreness, stress levels and the overall wellness scores (r=0.74-0.79, p<0.05). Discussion: The reduction of ITL improved the overall perceived wellness and sport-specific swimming performance of players. The abovementioned approach might be an effective training strategy in the lead-up to play-offs tournament providing useful and practical tool for screening changes in wellness and recovery status of the players.